Adsorption of Bisphenol A from Water Using Chitosan-Based Gels - Ludmila Aricov; Anca Ruxandra Leontieș (Gels)
The comonomer bisphenol A (BPA) finds applications in the plastics industry, where it is used in the production of polycarbonates, plastics, PVC, thermal paper, epoxy and vinyl ester resins, and polyurethane. The water, with which many of these materials come into contact, is one of the main sources of human exposure to BPA. When ingested or touched, BPA can damage organs, disrupt the endocrine and immune systems, generate inflammatory responses, and be involved in genotoxic processes. Therefore, the need to develop effective techniques for removing BPA from aqueous environments is imperative. This paper provides a comprehensive review regarding the effective removal of BPA from water, focusing on the performance and adsorption mechanisms of various adsorbents based on chitosan and chitosan composites. The chemical and physical factors, adsorption kinetics and models governing the adsorption process of BPA in chitosan materials are also examined. This review outlines that, despite considerable progress in the absorption of bisphenol using chitosan gels, further research is necessary to assess the efficacy of these adsorbents in treating real wastewater and in large-scale manufacture.